Measuring stress among hospital nurses: an empirical study using fuzzy evaluation. (6th September 2011) - Sinha, Tanuka Roy; Chatterjee, Debmallya; Iskanius, Päivi
One of the problems encountered by the employees in the place of work today is the increased level of work stress. In such scenario, the nursing profession is increasingly characterised by occupational stress leading to psychological and physical problems. Studies using fuzzy evaluation with special reference to government hospital nurses particularly in Indian context are very rare. Consequently, the paper tries to minimise the uncertainty in human judgement using triangular fuzzy numbers (TFNs). Findings show that among the major factors, dealing with the patients suffering from critical illnesses, lack of reward/recognition/apprehension and fatigue induces maximum stress among nurses.